Retrofitting and rehabilitation of damage footbridge over yamuna river - Shukla A.K.; Maiti P.R. (My University, 2025)
Every Structure has a certain predefined age with which it has to withstand, and after that, it requires the rehabilitation/repairing to avoid any damage or collapse. The footbridge over Yamuna River in Delhi, India was constructed in 1960 adjacent to Wazirabad barrage, and this is a very important link to East Delhi and West Delhi. Due to heavy traffic plying on this footbridge, in due course of time, the signs of deterioration were visible in the bridge expansion joint assemblies in the deck slab and cantilever portion of footpath slab. There were many potholes also developed in the wearing course. It was also dilapidation observed in many portions of the footpath, and some portion of the footpath slab were collapsed. The cantilever portion of the footbridge was retrofitted with steel jacketing fixing in the main longitudinal girder of the bridge. In this study analysis of the cantilever footbridge slab retrofitted by a steel jacket was carried out to check the deflection and stress limit of the bridge and it is found that the bridge is safe and now Bridge is open for traffic. © BEIESP.